Cyber Potential Metaphorical Map Method Based on GMap - Dongyu Si; Bingchuan Jiang; Qing Xia; Tingting Li; Xiao Wang; Jingxu Liu (ISPRS International Journal of Geo-Information)
Cyberspace maps facilitate the understanding of complex, abstract cyberspace. Due to the exponential growth of the Internet, the complexity of cyberspace has escalated dramatically. Traditional cyberspace maps are primarily for professionals and thus remain challenging for non-professionals to interpret. Ordinary users often find themselves overwhelmed by the vast amount of information and the complexity of cyberspace. This renders traditional visualization tools inadequate for the general public, thereby highlighting the urgent need for more intuitive and accessible representations. This study uses the metaphor of cyberspace as a familiar geographical space to simplify the understanding of its internal relationships. Based on Autonomous System (AS) connectivity data, a “node-link” model is created to illustrate cyber interactions and dependencies, forming a foundation for analysis. The GMap algorithm visualizes AS connectivity data of countries, converting it into an intuitive map that clearly illustrates the cyber composition and dynamics. Cyber potential and national influence are considered to enhance map practicality and accuracy. A cyber-geography metaphor model integrates scientific and geographical elements, improving readability. The optimized GMap algorithm includes a holisticcyberspace strength index, showing both connectivity and relative country strength in cyberspace. This metaphorical approach aims to reduce information complexity, making cyberspace more comprehensible to the general public.